2010
DOI: 10.1007/s11090-010-9223-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinations of Intermediate Neutral Species in Hydrocarbon Discharge Plasma

Abstract: This work reports laser ionization combined with Time-Of-Flight (TOF) mass spectrometry investigation on intermediate species in the hydrocarbon plasma of atmospheric-pressure fast-flow pulsed dc-discharge. All neutral intermediate species including transient radicals from benzene/Ar discharge have been characterized by a molecular beam sampling combined with TOF mass spectrometry. This shows that with a hydrocarbon gas mixture of 0.3% C 6 H 6 in Ar discharge the intermediate species consist of simple radicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Moving from Titan's atmosphere down to Earth, biphenyl and larger polyphenyls -in addition to PAHs and carbonaceous dust particles [14,15] -have been detected in the plasma treatment of gaseous mixtures containing benzene [16,17] as well as in the radiolysis of liquid [18,19,20] and gaseous benzene [21]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Moving from Titan's atmosphere down to Earth, biphenyl and larger polyphenyls -in addition to PAHs and carbonaceous dust particles [14,15] -have been detected in the plasma treatment of gaseous mixtures containing benzene [16,17] as well as in the radiolysis of liquid [18,19,20] and gaseous benzene [21]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…6 investigation with our apparatus has shown that the addition of Ar to the sampling gas had a significant influence in the detected species. We preliminarily consider the possible reason that leading to this result would be that the addition of the Ar gas had influenced the mechanism of plasma formation, due to the long lifetime and high energy of its metastable state Ar * , which has been suggested playing an important role in benzene discharge plasma in our previous work [20]. We can not perform any further discussion at present stage, since further confirmations and analyses must be needed to draw any accurate conclusion.…”
Section: Discussionmentioning
confidence: 93%
“…The design of our atmospheric fast-flow pulsed discharge plasma reactor has been described in previous publications [20], here only its main features are recalled. Typically, the input gas mixture is injected into discharge reactor at a backing pressure of 1-10 atmospheres by a pulse valve.…”
Section: Pulsed Plasma Reactormentioning
confidence: 99%